Exploring Cubosomes as an Emerging Approach of Novel Drug Delivery System: A Review - Amitha, N; Sandeep, DS; Rajanikant, P; Gowrav, MP; Kathirvel, S; Pradeep, HK; Jeyaprakash, MR (International Journal of Pharmaceutical Investigation, 2026)
Cubosomes are self-assembled nanostructures that exhibit a bicontinuous cubic phase. These nanoparticles can incorporate many drugs, including amphiphilic, hydrophilic, and lipophilic substances. The structure of cubosomes is typically analyzed using techniques such as NMR, electron microscopy, X-ray diffraction, and light scattering. Cubosomes, fabricated from biocompatible and biodegradable lipids such as phytantriol and monoolein, are considered safe drug delivery carriers. They are particularly effective in enhancing the solubility of poorly water-soluble drugs and offer site-specific drug delivery, a low dissociation rate, and improved drug retention. Common methods for preparing cubosomes include spray drying, ultrasonication, solvent evaporation, and hydrotrope. Cubosomes are widely used for ocular, transdermal, and oral drug delivery approaches as well as in cancer therapy.
Keywords: Cubosomes; Phytantriol; Spray drying; Particle size